ON THE PERSISTENCE OF SPATIAL ANALYTICITY FOR THE BEAM EQUATION - Dufera, Tamirat T.; Mebrate, Sileshi; Tesfahun, Achenef (Journal of Mathematical Analysis and Applications, 2022)
Persistence of spatial analyticity is studied for solution of the beam equation utt + (m + Δ2) u + |u| p−1u = 0 on Rn × R. In particular, for a class of analytic initial data with a uniform radius of analyticity σ0, we obtain an asymptotic lower bound σ(t) c/√t on the uniform radius of analyticity σ(t) of solution u(·,t), as t → ∞. © 2022 Elsevier Inc. All rights reserved
Keywords: Type of access: Open Access; Beam equation; Global well-posedness lower bound; Radius of analyticity Gevrey spaces